SERVICE QUALITY, PATIENT SATISFACTION, AND LOYALTY IN PRIMARY CARE: POLICY IMPLICATIONS FROM A NARRATIVE REVIEW - Panuturi Ratih Elizabeth Thresna Sinaga; Ratno Adrianto (Mulawarman International Conference on Tropical Public Health, 2025)
Background: Service quality is a key determinant of patient satisfaction and loyalty. While extensive evidence exists in hospital settings, findings in primary care remain fragmented, particularly in contexts undergoing health financing reforms. 1 Objective: This review aims to synthesize empirical evidence on the relationships between SERVQUAL dimensions, patient satisfaction, and patient loyalty in primary care settings. Methods: A narrative review was conducted on 34 primary empirical studies published between 2020 and 2025. Studies examining SERVQUAL dimensions—tangibles, reliability, responsiveness, assurance, and empathy—in relation to satisfaction and loyalty were included. Data were extracted and synthesized narratively, supported by an evidence frequency mapping. Results: Responsiveness, empathy, and tangibles consistently demonstrated strong associations with patient satisfaction. Satisfaction frequently mediated the relationship between service quality and loyalty, whereas direct effects of service quality on loyalty were inconsistent. Reliability and assurance showed variable effects across contexts. Most studies employed cross-sectional designs and SEM-PLS analytical approaches. Conclusion: Evidence supports a service quality–satisfaction–loyalty pathway in primary care. Contextual and financial factors, such as institutional financing models, may moderate these relationships and warrant further investigation using longitudinal and context-sensitive designs.